Forensic Assistance Project: Consultant Report 1999-027 Živinice I Republika Srpska Commission on Tracing Prisoners and Missing Persons - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: York, Heather On 15 June 1999 the Republika Srpska Commission on Tracing Prisoners and Missing Persons exhumed the remains of two individuals from two sites east of Živinice . Place of Exhumation: Živinice Exhumation Site: Jeginov Lug, Požarnica Date of Exhumation: 15 June 1999 Minimum Number of Exhumed Individuals: 002